Simultaneous tomographic particle image velocimetry and thermometry of turbulent Rayleigh–Bénard convection. (28th May 2021) - Schiepel, Daniel; Schmeling, Daniel; Wagner, Claus
Abstract: This paper presents a non-intrusive measurement technique for the simultaneous assessment of the three-dimensional (3D) velocity and temperature fields in thermal convection. The technique is based on the combination of tomographic particle image velocimetry and particle image thermometry. Thermochromic liquid crystal particles serve simultaneously as both flow tracers and thermometers. The velocity fields were measured in a volume of 62 500 cm 3 and the temperature fields in a subvolume of 20 000 cm 3 . Turbulent Rayleigh–Bénard convection in a water-glycol mixture at R a = 7.0 × 10 9 and P r = 18 was used as a model system to measure the instantaneous 3D velocity and temperature fields at the same time. Uncertainties of σ v ⩽ 0.66 mm s −1 for the velocity and σ t ⩽ 0.095  K for the temperature measurement were estimated corresponding to dynamic ranges of 24 and 21 levels, respectively. Correlating the measured temperature and velocity fields, it is shown that the obtained large-scale structure reflects a region of warm rising fluid which is well-known from the literature.